1990
DOI: 10.1111/j.1471-4159.1990.tb01952.x
|View full text |Cite
|
Sign up to set email alerts
|

α1‐Adrenergic Receptor Mediates Arachidonic Acid Release in Spinal Cord Neurons Independent of Inositol Phospholipid Turnover

Abstract: The alpha 1-adrenergic receptor has been shown to mediate the release of arachidonic acid in FRTL5 thyroid cells and MDCK kidney cells. In primary cultures of spinal cord cells, norepinephrine stimulated release of arachidonic acid (from neurons only) and turnover of inositol phospholipids (from neurons and glia) via alpha 1-adrenergic receptors. These two responses were dissociated by treatment with phorbol ester and pertussis toxin, which inhibited production of inositol phosphates with no appreciable effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 44 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…The physiologic role of 5-HT-receptor-stimulated release of arachidonic acid and subsequent eicosanoid formation in the hippocampus is not clear. Several other neurotransmitters have been shown to stimulate arachidonic acid mobilization in neurons, including norepinephrine, histamine, bradykinin, and glutamate (2)(3)(4)(5)36). Arachidonic acid and one of its lipoxygenase metabolites 12-hydroperoxy-5,8,10,14-eicosatetraenoic acid can inhibit ion conductances and cause presynaptic inhibition ofneurotransmitter release (37) presumably through inhibition of Ca2+/ calmodulin-dependent protein kinase II, a protein thought to be involved in neurotransmitter release (38).…”
Section: -Ht-stimulatedmentioning
confidence: 99%
See 1 more Smart Citation
“…The physiologic role of 5-HT-receptor-stimulated release of arachidonic acid and subsequent eicosanoid formation in the hippocampus is not clear. Several other neurotransmitters have been shown to stimulate arachidonic acid mobilization in neurons, including norepinephrine, histamine, bradykinin, and glutamate (2)(3)(4)(5)36). Arachidonic acid and one of its lipoxygenase metabolites 12-hydroperoxy-5,8,10,14-eicosatetraenoic acid can inhibit ion conductances and cause presynaptic inhibition ofneurotransmitter release (37) presumably through inhibition of Ca2+/ calmodulin-dependent protein kinase II, a protein thought to be involved in neurotransmitter release (38).…”
Section: -Ht-stimulatedmentioning
confidence: 99%
“…It is not clear from these studies whether the release of arachidonic acid is independent of inositolphospholipid turnover and whether the response is neural or glial in origin. Recent studies demonstrated a-adrenergic receptor stimulation caused arachidonic acid release from spinal cord, hippocampal, and cortical neurons, but not from glia cells, grown in primary culture that was independent of inositolphospholipid turnover (5).…”
mentioning
confidence: 99%
“…Thus, neither activation of phospholipase C nor a direct opening of receptormediated or voltage-dependent Ca 2+ channels appears to be involved in the ability of Ang II to release PGs in STTG1 and WITG2 and Ang-(l-7) in all three cell lines. In FRTL5 thyroid cells, 38 MadinDarby canine kidney (MDCK) cells 39 and spinal cord neurons, 40 a,-adrenergic agonists stimulate both inositol phospholipid hydrolysis and arachidonic acid release. However, enhancement of PG metabolism is dependent on extracellular Ca 2+ and most likely occurs through a Ca 2+ -dependent activation of phospholipase A 2 .…”
Section: +mentioning
confidence: 99%
“…Astrocytes are capable of converting AA into prostaglandins, leukotrienes and epoxygenase metabolites [22,27] and are also sensitive to feedback regulation by prostaglandins [28]. Notably, activation of many of the metabotropic receptors in astrocytes is associated with AA release and production of prostaglandins [29][30][31][32][33][34][35]. We have shown in astrocytes, which were activated by different stimuli, that AA is mainly released by the Ca 2+ -dependent PLA 2 (cPLA 2 ).…”
Section: Polyunsaturated Fatty Acids Astrocytes and Brain Functionsmentioning
confidence: 99%